An Analysis of Qibla Direction Tolerance According to Sheikh Muhammad Yasin Al-Fadani: A Solution to Qibla Deviation - Nur Mahmudi Qiromi; Ahmad Izzuddin; M. Basthoni (Astroislamica: Journal of Islamic Astronomy, 2026)
Determining the Qibla direction is a crucial aspect of performing the prayer (salat), particularly for Muslims living far from the Kaaba. Issues arise regarding whether one must face the exact structure of the Kaaba ('ayn al-Ka'bah) or if merely facing its general direction (jihat al-Ka'bah) is sufficient. This study aims to analyze the concept of Qibla direction tolerance according to Sheikh Muhammad Yasin al-Fadani as a solution to Qibla deviation, specifically within the context of mosques in the Nusantara (Malay Archipelago) region. This research employs a qualitative approach using a literature review method, examining the works of Sheikh Yasin alongside both classical and contemporary literature related to Islamic astronomy (ilmu falak). The results show that Sheikh Yasin proposes two scopes for the Qibla direction: jihat al-kubra (up to 180°) and jihat al-sughra (up to 90°), with a maximum tolerance of 45° to the right and left of the ideal direction. This view demonstrates the flexibility within classical Islamic jurisprudence (fiqh) regarding the limitations of measurement tools and observation methods in the past. Nevertheless, Sheikh Yasin consistently emphasizes the importance of Islamic astronomy and the mastery of scientific methods to determine a more accurate Qibla direction. In conclusion, Sheikh Yasin's perspective provides room for shari'i (legal) tolerance in determining the Qibla direction, while simultaneously emphasizing the urgency of utilizing modern technology to achieve greater precision in religious practices.